OLMo2 Architecture and Training Stability Effects on OLMoE-1B-7B Inference Throughput and Latency - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 2 peer-reviewed papers addressing the following research question: What is the impact of OLMo2's modified architecture and training stability techniques on the throughput and latency of inference for the OLMoE-1B-7B-0125-Instruction model across different hardware. 14 claims were extracted from source literature; 11 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 7.9/10. This report
Machine-generated literature synthesis.